2021
DOI: 10.1002/pmic.202000093
|View full text |Cite|
|
Sign up to set email alerts
|

Benchmarking accuracy and precision of intensity‐based absolute quantification of protein abundances in Saccharomyces cerevisiae

Abstract: Protein quantification via label-free mass spectrometry (MS) has become an increasingly popular method for predicting genome-wide absolute protein abundances. A known caveat of this approach, however, is the poor technical reproducibility, that is, how consistent predictions are when the same sample is measured repeatedly. Here, we measured proteomics data for Saccharomyces cerevisiae with both biological and inter-batch technical triplicates, to analyze both accuracy and precision of protein quantification vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Wiśniewski et al (2014) have attempted to overcome this limitation using the protein ruler, allowing a standardization to internal standards. A further limitation of the classical TPA (used in this study) is that the intensity corresponding to more than one protein (where a peptide is present in more than one protein) is assigned in full to each of those proteins (Sánchez, et al, 2021). A modification in the TPA can be performed by assigning such intensity on the basis of the ratio of intensity due to the razor peptides; this modification is more important in limiting overestimation of individual proteins than in addressing the global overestimation .…”
Section: Discussionmentioning
confidence: 99%
“…Wiśniewski et al (2014) have attempted to overcome this limitation using the protein ruler, allowing a standardization to internal standards. A further limitation of the classical TPA (used in this study) is that the intensity corresponding to more than one protein (where a peptide is present in more than one protein) is assigned in full to each of those proteins (Sánchez, et al, 2021). A modification in the TPA can be performed by assigning such intensity on the basis of the ratio of intensity due to the razor peptides; this modification is more important in limiting overestimation of individual proteins than in addressing the global overestimation .…”
Section: Discussionmentioning
confidence: 99%
“…These absolute error values are comparable to those of the commercial kit READYBEADS™ (ANAQUANT, Villeurbanne, France), which is used to quantify absolute abundance with a BSA standard at different concentrations [ 47 ]. Another study indicated that TPA could be preferentially employed because it yielded similar results to those of the UPS2-based strategy when used with iBAQ applied to a single yeast sample [ 19 ]. This finding fits with the accuracy among samples observed in our study ( Figure 3 ); it contrasts with what we observed for the absolute error of the external proteins ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…However, the protein abundances calculated using TPA might be wide of the mark since, in general, more than 60% of peptide fragments are not assigned at the protein identification stage. While numerous studies have applied various forms of TPA [ 19 , 20 , 21 , 22 , 23 ], it remains to be determined whether this strategy accurately estimates protein abundance. Second, there is a commonly employed strategy that relies on an external standard, the Universal Proteomics Standard 2 (UPS2).…”
Section: Introductionmentioning
confidence: 99%
“…Tear film liquid samples were collected and prepared for the discovery proteomic analysis in SONAR (data-independent mode) on a high-resolution quadrupole time-of-flight mass spectrometer. Confidently identified proteins were quantitatively assessed using Universal Proteomic Standard sample (UPS-2, Dynamic range) designed for quantitative proteomic assay [ 58 ]. The accumulated set of proteins were analyzed using a GO terms enrichment tool REVIGO [ 59 ] and Resnik’s semantic similarity approach [ 60 ].…”
Section: Methodsmentioning
confidence: 99%